The 2nd Balinese Language Month: to raise Society awareness on the Balinese Language - I Gede Mas Suputra (Bali Tourism Board, 2020)
On February 1st, 2020, Bali Governor Wayan Koster scheduled to open the 2nd Balinese Language Month at the Ksirarnawa Building, Art Centre, Denpasar as an implementation of Bali Governor's Regulation No. 80 of 2018, concerning the Protection and the usage of Language, Literacy, and Balinese Literature & the Implementation of the Balinese Language Month. The Balinese Language Month imbued the spirit of language preservation. The event is strongly related to the apprehensive fact that the Balinese's interest in using their native language is plummeting significantly over the years. The festival was successfully held and gathered significant attention from the public. It is suggested to conduct follow up research to measure the public's heed after the Balinese Language Festival or any similar events. Should the public's favour in learning and using their native discourse increases, then the program should be treated as a frontline in preserving the language. However, when the festival turned out did not make any significant change in society, perhaps a better strategy should be considered in generating social awareness in their mother language. Furthermore, the research might be as well acts as input for the committee; on this occasion, the provincial Government of Bali to keep on improving the quality of the language preservation festival.